ANALISA EMISI GAS BUANG DARI PENGGUNAAN BAHAN BAKAR CAMPURAN BIODIESEL JARAK PAGAR DAN SOLAR PADA BOILER - Mariyamah Mariyamah (Bioilmi: Jurnal Pendidikan, 2016)
Policy of national energy that is with releasing of Perpres No. 5 The year 2006 and has been strengthened it with Permen ESDM number 12 the year 2015 where usage of biodesel in the year 2025 can reach 30 % from the requirement either from transportation sector, household and also industry causing claims to be able to soon is realized. Fuel consumption biodiesel has been applied intransportation while fuel consumption in industry especially boiler till now has not been publication. Where boiler is a real industrial equipment determines in process of industry, especially at chemistry, fertilizer & petrochemical, oil & gas, and other manufacture. Research applies mixture fuel biodiesel from jatropha curcas and solar as a fuel of boiler. And after that analysed exhaust emission of gas (CO, CO2, HC, NOx and smoke) with fuel mixture ratio between diesel fuels and biodiesel of jatrpoha curcas (B5, B10, B15, B20). Research to fuel mixture between diesel fuels and jatropha curcas biodiesel in the steady state gives result that exhaust gas of emission smoke of decreasing, flue gas temperature increases, CO2 yeilded decreases, CO is not seen, low HC, NOx increases at the height of mixture ratio jatropha curcas biodiesel in diesel fuel